Confessions of a Free Speech Lawyer Charlottesville and the Politics of Hate - Smolla, Rodney A. (Cornell University Press, 2020)
In the personal and frank Confessions of a Free Speech Lawyer, Rodney A. Smolla offers an insider's view of the violent confrontations in Charlottesville during the "Summer of Hate." Blending memoir, courtroom drama, and a consideration of the unresolved wound of racism in our society, he shines a light on the conflict between the value of free speech and the protection of civil rights.Smolla has spent his career in the thick of these tempestuous and fraught issues, from acting as lead counsel in a famous Supreme Court decision challenging Virginia's anti-cross burning law, to being co-counsel in a libel suit brought by a fraternity against Rolling Stone magazine, for publishing an article alleging a gang-rape initiation ritual. And yet, he has also been active as a university leader, where he has served as Dean of three law schools and President of one, railing against hate speech and sexual assault on American campuses.Well before the tiki torches cast their ominous shadows across the nation, the city of Charlottesville sought to relocate the "Unite the Right" rally; Smolla was approached to represent the alt-right groups. Though he declined, he came to wonder what his history of advocacy had wrought. Feeling unsettlingly complicit, he joined the Charlottesville Task Force, where he realized that the events that transpired had meaning and resonance far beyond a singular time and place. Why, he wonders, has one of our foundational rights created a land in which such tragic clashes happen all too frequently?